The surgical-based treatment of malignant pleural mesothelioma: a literature review of a still ongoing debate - FuriaSimone; VerderiEnrico; NataleGiuseppe; CavallinRoberta; LoGiudiceFabio; FerronatoAndrea; BredaCristiano (中华胸部外科电子杂志, 2022)
Background and Objective: Pleural mesothelioma is an aggressive disease with poor prognosis due to the tendency to relapse. Despite the lack of uniform protocols of therapy, surgery remains the cornerstone of multimodal treatment. Nevertheless, the debate on which is the optimal choice for surgical-based approach lasts over time and is based over the oncological benefits of obtaining a theoretical greater radicality rather than preserving the anatomical integrity in view of further treatments. This review is intended to summarize the topics of this dispute still ongoing. Methods: A review on the PubMed/Medline literature database of the different surgical approach was carried out, screening all the publications in English from 2000 to 2021. The search strategy has been focused on comparative studies of surgical techniques to understand if and how the choice of the type of surgery to be offered in the forefront has changed over the years. Key Content and Findings: Within the multimodal strategy the goal of surgery, performed with radical intent, is to achieve the macroscopic complete removal. Two procedures are aimed to this purpose: the lung-sacrificing surgery as the extrapleural pneumonectomy and the lung-sparing surgery as the pleurectomy/decortication extended or not to resection/reconstruction of diaphragm and pericardium. Many centers today have abandoned the most radical procedure in favor of the most conservative, but the superiority of one technique over the other remains controversial. Conclusions: In the absence of comparative randomized trials, the choice of surgical technique is determined by the experience of individual centers and by the attitude of surgeons. Further research is needed to standardize treatment protocols and to define the role of surgery in the context of multimodal therapy.